Effect of Methanol Stem Bark Extract of Annona senegalensis on Haematological Profile in Diethylnitrosamine-Induced Hepatocellular Carcinoma in Rats - Umaru, Isaac John; Philemon, Panah; Akem, Ingwu Joseph; Omolara, Mosugu Ovayoza; Okang, Ogar Fonne; Tansaba, Akafa Andes; Philip, Shadrach; Frank, Otashu Kenneth (Darul Yasin Al Sys, 2025)
Liver cancer, particularly hepatocellular carcinoma (HCC), is a leading cause of mortality worldwide and is frequently associated with hematological complications such as anemia and impaired blood clotting. This study evaluated the hematoprotective effects of methanol stem-bark extract of Annona senegalensis in rats with diethylnitrosamine (DEN)-induced HCC. Fifty-four male rats were allocated into six groups: a normal control group, a DEN-induced group without treatment, a positive control group treated with silymarin, and three treatment groups administered varying doses of A. senegalensis extract. Hematological parameters assessed included red blood cells (RBC), hemoglobin (HGB), white blood cells (WBC), hematocrit (HCT), and platelets (PLT). DEN induction significantly reduced RBC, HGB, and PLT levels, indicating anemia and coagulation impairment. Treatment with A. senegalensis, particularly at 400 mg/kg, markedly improved these hematological indices, suggesting a restorative effect on blood parameters. The protective role of the extract may be attributed to its bioactive constituents, such as flavonoids, alkaloids, and tannins, known for their antioxidant and anti-inflammatory activities. These findings suggest that A. senegalensis possesses promising hematoprotective potential in the management of blood-related complications associated with liver cancer. Further research, including mechanistic studies and clinical trials, is warranted to validate its safety and therapeutic efficacy in humans.